Meningkatkan Kemampuan Menganalisis Struktur Teks Tanggapan Menggunakan Model Think Talk Write Siswa Kelas VII B SMP Negeri 15 Palu - Andi Sriwulan Ashari Hardy; Pratama Bayu Santosa; Herni Sahid (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
This research is a Classroom Action Research (CAR). This research aims to improve the ability to analyze the structure of response texts of class VII B students of SMP Negeri 15 Palu through the Think Talk Write Learning Model. This type of research was carried out in two cycles, namely cycle I and cycle II, each cycle has planning, action implementation, observation and reflection. The subjects in this study were class VII B students of SMP Negeri 15 Palu with a total of 25 students. Data collection techniques used were documentation, tests, and observations. All data obtained were analyzed using qualitative and quantitative descriptive. The results of this study indicate that the ability to analyze the structure of response texts of class VII B students in each cycle increased. Based on data in the pre-cycle, the completeness of student learning outcomes was only 23 students with a percentage of 92% of 25 students. After implementing the cycle I by applying the Think Talk Write model, students were able to obtain grades according to the Minimum Completion Criteria (KKM) as many as 15 students with a percentage of 60%. Then in cycle II the number of students who were able to obtain grades according to the Minimum Completion Criteria (KKM) increased to 23 students with a percentage of 92%. Thus, it can be concluded that using the Think Talk Write method can improve the ability to analyze the structure of response texts of Class VII B students of SMP Negeri 15 Palu.